La adaptación de la radio tradicional al entorno digital: caso radio pública UTMach. - Escobar Sanchez, Mayra Estefania; Espinoza Mendoza, Stephany Katherine (Machala, 2021)
Traditional media are very important in the communication environment, since they are mass media that serve to inform the community, but with the appearance of the internet the traditional media would begin to change their course, since as time passes, things are taking different perspectives, more for traditional media, because we must bear in mind that as technology continues to evolve, native digital media that were born in this digital environment began to appear 4 or 5 years ago and therefore are media that are handled with the different digital platforms, whether social networks, blog, among others, so this forces the traditional media to adapt to this new digital environment, so as not to be forgotten, implementing different communication strategies to survive these new digital platforms. Nowadays several radio media have managed to adapt to the digital world in order to provide the audience with visual, innovative and creative content, said this, the following research project is born, where its objective is to analyze the process of adaptation of the Utmach Public Radio to the digital environment, of the city of Machala, Ecuador. To achieve the results of this research, the mixed methodology of quantitative-qualitative was used, from the point of view of quantitative, the content analysis of the fanpage of the Public Radio Utmach was carried out, to know the different communication strategies applied, likewise a clipping of the programming grid and its publications was elaborated, to know the impact of the audience, a survey was prepared with 9 questions, under a range of ages from 16 to 56 years. On the other hand, in the qualitative methodology, interviews were conducted with different professionals in the field of digital culture and social communicators in order to know what would be the communication strategies that a traditional media can implement to adapt to the online medium. Likewise, after having applied the different research methodologies, through the analysis of content, it was obtained that it is important to be innovative, that immediacy is not necessary but rather to present good quality content to the audience, since the publications and the various programs seek to complement the use of audiovisual and the strength of the comment to generate awareness in the audience that consumes this digital medium. Regarding surveys, 50% of its community considers that the contents broadcast are interactive and that they prefer to be informed through videos, likewise the respondents prefer the utmach informa program since through it they learn about what is happening in the world. The interviews carried out with the different professionals in communication and digital culture leave as a result it is important to carry out a previous analysis of the medium, to identify their audience and be today very creative implemented, podcast, infographics, reports to the digital medium to achieve greater impact on the audience, just as it is important the adaptability of the contents implemented in the different digital platforms that the medium counts.
Los medios tradicionales son muy importantes en el entorno de la comunicación, ya que son medios masivos que sirven para información a la comunidad, pero con la aparición del internet los medios tradicionales empezarían a cambiar su rumbo, ya que a medidas que el tiempo pasa, las cosas van tomando diferentes perspectivas, más para los medios tradicionales, porque hay que tener en cuenta que conforme la tecnología sigue evolucionando, empezaron aparecer hace 4 o 5 años atrás, los medios digitales nativos que nacieron en este entorno digital y por ende son medios que se manejan con las diferentes plataformas digitales, ya sean redes sociales, blog, entre otros, entonces esto obliga a los medios de comunicación tradicional a adaptarse a este nuevo entorno digital, para no quedar en el olvido, implementando diferentes estrategias comunicacionales para sobrevivir a estas nuevas plataformas digitales. Hoy en día varios medios radiofónicos han logrado adaptarse al mundo digital con el fin de brindar a la audiencia contenidos visuales, innovadores y creativos dicho esto nace el siguiente proyecto de investigación, donde su objetivo es analizar el proceso de adaptación de la radio Pública Utmach al entorno digital, de la ciudad de Machala, Ecuador. Para lograr llegar a los resultados de esta investigación, se utilizó la metodología mixta de cuanti-cualitativa, desde el punto de vista de cuantitativa se realizó el análisis de contenido de la fan Page de la Radio Pública Utmach, para conocer las diferentes estrategias comunicacionales aplicadas, así mismo se elaboró un clipping de la parrilla de programación y sus publicaciones, para conocer el impacto que tiene la audiencia se elaboró una encuesta con 9 preguntas, bajo un rango de edades de edades de 16 a 56 años. Por otro lado, en la metodología cualitativa se realizaron entrevistas a diferentes profesionales en el campo de la cultura digital y comunicadores sociales con el fin de conocer cuáles serían las estrategias comunicacionales que un medio tradicional puede implementar para adaptarse al medio online. Así mismo luego de haberse aplicado las diferentes metodologías de investigación, mediante el análisis de contenido, se obtuvo que es importante ser innovador, que no es necesario la inmediatez sino más bien presentar contenido de buena calidad a la audiencia, ya que las publicaciones y los diversos programas busca complementar el uso del audiovisual y la fuerza del comentario para generar conciencia en la audiencia que consume este medio digital. Con relación a las encuestas, el 50% de su comunidad considera que los contenidos emitidos son interactivos y que prefieren informarse a través de videos, así mismo los encuestados prefieren el programa Utmach informa ya que mediante él se enteran de lo que pasa en el mundo. Las entrevistas realizadas a los diferentes profesionales en comunicación y cultura digital dejan como resultado es importante realizar un análisis previo del medio, para identificar su público y ser hoy en día muy creativos implementado, podcast, infografías, reportajes al medio digital para lograr tener mayor impacto en la audiencia, al igual que es importante la adaptabilidad de los contenidos implementados en las diferentes plataformas digitales que el medio cuente.
Keywords: ADAPTACION; MEDIO TRADICIONAL; MEDIO DIGITAL; PLATAFORMA DIGITAL